Cooperation Maxim Error Principles and Implications on Warintil Official Series “Ga Boleh Souzon” - Yosi Maeleona Passandaran; Yulia Sofiani Zaimar; Leni Tiwiyanti (Pujangga: Jurnal Bahasa dan Sastra, 2022)
This article would like to describe the error of maxims and also the meaning of implicatures in the sitcom of Kontrakan Rempong from Warintil Official on Youtube. There were five types of violations of the cooperative principle caused by the speech participants.  The research method used in this research is descriptive qualitative. The data is taken from Kontrakan Rempong, titled “Gak Usah Souzon”.  The collecting data are using the documentation method by listening and note-taking techniques from the Kontrakan Rempong’ characters' conversation. Meanwhile, the object of this research is the form and meaning of implicature in humour Kontrakan Rempong. The results of this research indicate the form of conversational implicatures that function as a supporter of humour in humorous discourse, they are:  the Youtube  Kontrakan Rempong has a violation of the maxim of the cooperative principle. In the maxim of quality, there are two categories of violations; they are the words that are used solely to show her or his arrogance and to make the main character a fool. In other words, the error maxim is seemed as trying to evade responsibility. The function of violation of the Maximal Principle of cooperation has been categorized based on existing data like wisdom maxim, acceptance maxim, humility maxim, quality maxim, approbation maxim and quantity maxim. The maxims error is the error of quantity maxim, quality maxim, wisdom maxim approbation and humility maxim. In addition to supporting humour, the error causes many implications related to human nature and real life.Keywords: humour, error, maxim, implicature